2018
DOI: 10.15252/emmm.201809024
|View full text |Cite
|
Sign up to set email alerts
|

Targeting miR‐223 in neutrophils enhances the clearance of Staphylococcus aureus in infected wounds

Abstract: Argonaute 2 bound mature microRNA (Ago2‐miRNA) complexes are key regulators of the wound inflammatory response and function in the translational processing of target mRNAs. In this study, we identified four wound inflammation‐related Ago2‐miRNAs (miR‐139‐5p, miR‐142‐3p, miR‐142‐5p, and miR‐223) and show that miR‐223 is critical for infection control. miR‐223 Y/− mice exhibited delayed sterile healing with prolonged neutrophil activation and interleukin‐6 expression, and markedly improved repair of Staphylococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 64 publications
0
52
0
1
Order By: Relevance
“…Based on the available data, miR-223 is involved in the subtle control of different pathological conditions, ranging from inflammation [ 186 , 187 , 188 ] to infection [ 189 ] and cancer [ 190 ]. Neutrophils are an essential part of the innate immune response as they are critical for the first line of defense against bacteria and fungi.…”
Section: Micrornas Altered In Diabetic Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the available data, miR-223 is involved in the subtle control of different pathological conditions, ranging from inflammation [ 186 , 187 , 188 ] to infection [ 189 ] and cancer [ 190 ]. Neutrophils are an essential part of the innate immune response as they are critical for the first line of defense against bacteria and fungi.…”
Section: Micrornas Altered In Diabetic Wound Healingmentioning
confidence: 99%
“…Neutrophils are an essential part of the innate immune response as they are critical for the first line of defense against bacteria and fungi. De Kerckhove and colleagues showed that miR-223 is expressed in neutrophils, controlled by the transcription factor c/EBPα and it represses IL6 production, therefore restraining neutrophil activation and allowing S. aureus growth in wounds [ 189 ]. Consequently, knock-down of miR-223 using anti-sense oligonucleotides improves wound-healing [ 189 ].…”
Section: Micrornas Altered In Diabetic Wound Healingmentioning
confidence: 99%
“…*P , 0.05, **P , 0.01, ***P , 0.001. migration, and invasion in gastric cancer (27). We further elucidated the function of miR-223 in skin wound healing by analyzing miR-223 knockout mice (28). Similarly, miR-31 was highly expressed during the transition from the inflammatory to the proliferative phase in an in vivo human skin wound healing model, and the overexpression of miR-31 promoted cell proliferation and migration in human primary keratinocytes (29).…”
Section: Discussionmentioning
confidence: 99%
“…While it is today well accepted that miRNAs can function as critical regulators of tissue repair (Luan et al , ), the specific miRNAs involved and the wound healing phases during which they primarily function remain unclear in many cases. In this issue of EMBO Molecular Medicine , de Kerckhove et al () describe a novel approach to identify functional miRNAs that are elevated in response to skin injury and identify miRNA‐223 (miR‐223) as a potential therapeutic target able to influence acute inflammation in S. aureus‐ infected wounds (Fig ).…”
Section: Targeting Mir‐223 Increases Neutrophil Activation In Infectementioning
confidence: 99%
“…Targeting specific miRNAs represents a promising strategy as a means of fighting different pathologies. In their study, de Kerckhove et al () investigate the therapeutic potential of targeting miR‐223 during wound healing using mice with a specific deletion of miR‐223 (miR‐223 Y/− ). Live imaging revealed increased recruitment of neutrophils in miR‐223 Y/− mice as early as 12 h post‐injury.…”
Section: Targeting Mir‐223 Increases Neutrophil Activation In Infectementioning
confidence: 99%